2015
DOI: 10.1128/jcm.03068-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Characterization of Uropathogenic Escherichia coli from an Outpatient Urology Clinic in Rural Japan

Abstract: gIn the remote Japanese community of Saku, a rural town in the Nagano Prefecture, a large proportion of outpatient urinary tract infections was caused by well-recognized globally dispersed clonal lineages of uropathogenic Escherichia coli (UPEC). However, most of these strains were drug susceptible, suggesting that factors other than selection pressure account for the clonal spread of drug-susceptible UPEC. In Japan, most characterizations of uropathogenic Escherichia coli (UPEC) strains have been limited to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Moreover, ST95 and ST73, both HIF STs, had lower resistance rates than non-HIF STs, which indicates that antimicrobial resistance is not always required to become a common ST. This finding is consistent with previous reports [ 24 , 30 ], in which ST95 was the most common genotype and the strains of ST95 were mostly susceptible to all tested drugs. The prevalence of drug-susceptible isolates of ST95, ST73 and ST357, which together accounted for 57% (74/129) of all susceptible isolates, appears to have lowered the overall rate of antimicrobial resistance (22.3%) of the UPEC isolates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, ST95 and ST73, both HIF STs, had lower resistance rates than non-HIF STs, which indicates that antimicrobial resistance is not always required to become a common ST. This finding is consistent with previous reports [ 24 , 30 ], in which ST95 was the most common genotype and the strains of ST95 were mostly susceptible to all tested drugs. The prevalence of drug-susceptible isolates of ST95, ST73 and ST357, which together accounted for 57% (74/129) of all susceptible isolates, appears to have lowered the overall rate of antimicrobial resistance (22.3%) of the UPEC isolates.…”
Section: Discussionsupporting
confidence: 93%
“…UPEC strains can be transmitted via water, food [ 25 ], or through person-to-person contact [ 5 , 27 , 28 ]. However, the water supply in Takikawa is monitored strictly according to the Drinking Water Quality Standards of Japan, which includes ‘ E. coli , not to be detected.’ Although previous studies [ 29 , 30 ] reinforced within-household transmission, the absence of geographical case concentration suggested that acute UTIs less frequently occurred in women living together with the patients than expected. This can be explained partly by the growing trend toward living in nuclear families (i.e., small family size) and by a feature of the pathogenesis of acute UTIs.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, these same genotypes (ST95, ST127, ST73, ST69, ST131, and ST10) account for a large proportion of both CA-UTI and bloodstream infections (BSI) in many other communities around the world (12)(13)(14)(26)(27)(28). The predominance of these major genotypes varies geographically.…”
Section: Discussionmentioning
confidence: 99%